Ancient Caesarea Brought to Life - Rife, Joseph L. (The Biblical archaeology review, 2021)
This book takes its title from the poignant words of Hannah Szenes, who lived in a kibbutz just south of the ancient coastal city of Caesarea Maritima and was executed by the Nazis during a clandestine operation in Europe to save Hungarian Jews. The haunting poem, which remains so powerful in the collective consciousness […]